The success rate of posterior tibial nerve block in the ankle with and without ultrasound guidance: A clinical trial study for pain management in emergency departments - Behrang Rezvani Kakhki (Journal of Emergency Practice and Trauma, 2021)
Objective: The purpose of the current study was to assess the success rate of posterior tibial nerve block in the ankle with and without ultrasound guidance for pain management in emergency departments. Methods: This clinical trial was conducted on 80 individuals who needed posterior tibial nerve block in the ankle at the emergency department of Hashemi Nejad hospital and Edalatian emergency center in Mashhad, Iran. The eligible individuals were randomly assigned to one of two groups, designated the control (landmark-based nerve block) and the case group (ultrasound-guided nerve block). The two groups were compared in terms of the main measurable outcomes. The data were analyzed using SPSS software (version 20) by nonparametric tests. Results: According to the findings, the mean and median of nerve block success in the landmark-based and ultrasound-guided methods were significantly different between the two groups, both 15 (P=0.02) and 30 (P=0.001) min post-intervention. In this regard, nerve block with ultrasound guidance had a higher success rate compared to the landmark method. However, no significant difference between the two interventions was found in terms of the mean and median of the procedure duration (P=0.8) and injection frequency (P=0.4). On the other hand, the two groups were significantly different regarding the median and mean of patient satisfaction (P=0.00), duration of analgesia (P=0.004), and nerve block-related complications (P=0.03). Conclusion: The findings revealed that the relatively new technique of nerve block by ultrasound-guide resulted in better outcomes than the landmark-based method. Consequently, this method could be adopted to control acute pain in the emergency departments and improve patient care.